The power of purpose. Issue 3 (6th June 2019) - Renshaw, Ben
Abstract : Purpose: This paper aims to offer evidence-based advice for leaders on how to be purpose-led and how to use ones purpose to create more opportunity, to become a better leader and to establish a clear sense of direction and conviction at work and in life. Design/methodology/approach: By asking the right questions, implementing seven key principles and creating a purpose statement, employees, employers and businesses can identity their purpose, achieve more satisfying results establish a clearer sense of purpose and become better leaders. Findings: A statement of purpose will give a person more direction and promise a future of more fulfillment, more inspiration and more success. Originality/value: Reaching goals and attaining success is complicated and personal, but these tools offer practical, proven tips and strategies for uncovering one's purpose and living out one's purpose on a daily, monthly and yearly manner.